2020
DOI: 10.3389/fonc.2020.606436
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Autophagy Functions Shape the Tumor Microenvironment and Play a Role in Cancer Progression - Implications for Cancer Therapy

Abstract: The tumor microenvironment (TME) is a complex environment where cancer cells reside and interact with different types of cells, secreted factors, and the extracellular matrix. Additionally, TME is shaped by several processes, such as autophagy. Autophagy has emerged as a conserved intracellular degradation pathway for clearance of damaged organelles or aberrant proteins. With its central role, autophagy maintains the cellular homeostasis and orchestrates stress responses, playing opposite roles in tumorigenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 228 publications
0
31
0
Order By: Relevance
“…TME is the key regulator of carcinogenesis and consists of tumor cells, stromal cells, and immune cells (13,14). TICs are closely associated with tumorigenesis, angiogenesis and the growth and metastatic potential of tumor cells, which could alternately modulate the pattern of immune cells (15)(16)(17)(18). Now, immunotherapy has been widely used to treat a broad spectrum of cancers including BRCA (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…TME is the key regulator of carcinogenesis and consists of tumor cells, stromal cells, and immune cells (13,14). TICs are closely associated with tumorigenesis, angiogenesis and the growth and metastatic potential of tumor cells, which could alternately modulate the pattern of immune cells (15)(16)(17)(18). Now, immunotherapy has been widely used to treat a broad spectrum of cancers including BRCA (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some recent data indicated that radioresistance appeared to be most closely associated with senescence occurring earlier and more significant in the p53wt NSCLC cells [ 99 ]. In the light of a tumor dormancy model, a phase of proliferative recovery in a subset of cells frequently following after the radiation-induced senescence can contribute to therapy resistance and conceivably the disease relapse [ 100 , 101 ]. In this regard, such an impact of senescence will open up a new avenue for novel senolytics that await clinical prove as an adjuvant to radiotherapy to prolong remission by delaying disease recurrence in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Reprogramming the matrix component of the TME could enhance the antitumor effects of available therapies. Matrix mediators' effects on autophagy and apoptosis could also be recruited in an ongoing effort to harness these processes for new therapeutic strategies [237,238]. Therefore, as new agents are continuously developing, such as anti-tumor-specific antibodies or even specific CAR-T cells, matrix-derived approaches can be part of the combinatorial strategies that enhance antitumor responses.…”
Section: Data From Clinical Trials Focusing On Targeting the Igf-irmentioning
confidence: 99%